Effect of microplastics on the allelopathic effects of native and invasive plants on co-occurring invaders - Yuan, Ling; Zhou, Li; Li, Junmin (Frontiers in Plant Science, 2024)
Introduction Microplastic pollution has emerged as a significant global change factor, with the potential to alter the biological, physicochemical properties of soil and to subsequently affect plant growth. Despite growing recognition of the impacts of microplastic pollution, the mechanisms by which microplastics modify plant leaf chemistry and influence allelopathic interactions among co-existing plant species remain unclear. Methods We used the native perennial forb Achyranthes bidentata and the invasive annual forb Amaranthus spinosus as focal species. We grew the two species with and without competition with each other. This setup was further combined with a treatment involving the addition of polyethylene (PE). We then testd the effects of aqueous extract on seed germination and seedling growth for five invasive and five native species. Subsequently, metabolomic analysis was conducted on the aqueous extracts, in which significant allelopathic effects were observed on test species. Results and discussion The presence of PE microplastics enhanced the biomass of both Achyranthes and Amaranthus under competitive and non-competitive growth conditions. Furthermore, PE microplastics were found to induce a negative allelopathic effect for the native plant Achyranthes on co-occurring plants, which appeared to be mediated through changes in leaf chemistry. Bisdemethoxycurcumin, ethylparaben, salicin 6’-sulfate and 5-hydroxy-3’,4’,7-trimethoxyflavone glucoside were proven important compounds for allelopathic enhancement. Overall, these results suggest that microplastic pollution has the capability to influence the co-existence of invasive and native plants by altering their allelopathic potential. This insight into the interactions between microplastics and plant allelopathy provides a novel perspective on how microplastic pollution could modify plant species interactions and ecosystem dynamics. Future studies could aim to answer how microplastics might affect plant root exudates and whether this process would mediate biological invasion.